Surgical treatment of congenital cystic adenomatoid malformation: a retrospective study of single tertiary center experience. (16th February 2017) - Xia, Bo; Yu, Gang; Liu, Cuifen; Hong, Chun; Tang, Jing
Abstract: Objective : To summarize the experience drawn from treatment of fetus with congenital cystic adenomatoid malformation (CCAM). Methods : This retrospective report has reviewed a clinical history of 115 patients with CCAM from September 2012 to June 2014. All cases were divided into two groups according to symptomatology: group A ( n  = 96, asymptomatic group) and group B ( n  = 19, symptomatic group). Major factors were compared between two groups. Numerical data were presented as the median (range). The difference between median was performed with ANOVA. Results : The mean gestational age of prenatal diagnosis was 24.3 weeks (range, 17–36). 49 cases with CCAM volume ratio (CVR) were retrospectively analyzed, with a median max CVR of 0.95 (range, 0.19–3.2), In the 115 cases, mean operation age was (3.7 ± 0.32) months old. Symptom is significantly associated with lesion size and chest radiographs (CXR) ( p < 0.05). Compared with symptomatic CCAM patients, asymptomatic patients were associated with better clinical outcome. Conclusions : The value of CVR to evaluate prognosis showed no statistical significance. Although CXR are not reliable indicators to assess the lesion, it can predict the emergency situation. Due to potential trend of symptomatic and poor postoperative symptoms group, early postnatal CT scan and early surgical treatment are suggested.